Thermobarometry of the Leo Pargil Dome, NW India: Insights into Exhumation of Mid-Crustal Rocks in the Himalaya - Nicholas Costello (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
In the Himalayan orogen, the foreland is dominated by thrust faults, which accommodate north-south crustal shortening associated with continent-continent collision. The interior of the orogen, however, is dominated by east-west extension, which in the highly compressional Himalaya remains a process that is poorly understood. This study aims to improve this understanding by quantifying the exhumation history of metamorphic rocks associated with the Leo Pargil Dome, a prominent extensional feature located on the southern margin of the Tibetan Plateau. By examining extensional features and the exhumation history of associated metamorphic rocks, valuable insights such as the chronology and kinematics of the extensional processes can be understood. Mineral assemblages and the elemental composition of specific minerals record the pressures and temperatures to which rocks have been subjected, allowing direct quantification of exhumation history by thermobarometry. In this study, a sample from the hanging wall of the Leo Pargil shear zone (LPSZ) was analyzed using conventional light microscopy, as well as an electron microprobe. The sample contained quartz, plagioclase, muscovite, biotite, and garnet, with garnets exhibiting prograde compositional zoning, and biotite and muscovite showing homogeneous elemental compositions. Temperature estimates were calculated using garnet-biotite geothermometry, whereas pressure estimates were calculated using garnet-biotite-muscovite-plagioclase geobarometry, with all calculations performed by Geothermobarometry (GTB) computer software. Results indicate that rocks from the hanging wall of the LPSZ were subjected to temperatures ranging from 500 to 635°C and pressures between 6.8 and 9.2 kbar prior to exhumation. Assuming a lithostatic pressure gradient of 3.7 km/kbar, this sample was exhumed from a depth of 25-34 km. The constraint of these pressures and temperatures, as well as an estimated depth from which the sample was exhumed, allows future researchers a better understanding of extensional processes in the Himalayas.